The art of computer programming Volume 2 Seminumerical Algorithms - Knuth, Donald E. (Boston Addison-Wesley, 1997)
The book summarizes the major paradigms and basic theory of such algorithms, thereby providing a comprehensive interface between computer programming and numerical analysis. Particularly noteworthy in this third edition is Knuth's new treatment of random number generators, and his discussion of calculations with formal power series.
Includes bibliographical references and index
Keywords: Công nghệ thông tin